The Transmission of Learning in Islamic Africa - Reese, Scott, (Brill Book Archive Part 1, ISBN: 9789004472495., 2004)
In a series of essays this collected volume challenges much of the conventional wisdom regarding the intellectual history of Muslim Africa. Ranging from the libraries of Early Modern Mauritania and Timbuktu to mosque lectures in contemporary Mombasa the contributors to this collection overturn many commonly accepted assumptions about Africa's Muslim learned classes. Rather than isolated, backward and out of touch, the essays in this volume reveal Muslim intellectuals as not only well aware of the intellectual currents of the wider Islamic world but also caring deeply about the issues facing their communities.